2023
DOI: 10.1002/smll.202300687
|View full text |Cite
|
Sign up to set email alerts
|

Watermelon Flesh‐Like Ni3S2@C Composite Separator with Polysulfide Shuttle Inhibition for High‐Performance Lithium‐Sulfur Batteries

Abstract: The shuttle effect limits the practical application of lithium‐sulfur (Li‐S) batteries with high specific capacity and cheap price. Herein, a three‐dimensional carbon substrate containing Ni3S2 nanoparticles is created to modify the separator. The in situ optical visualization battery proves that the material can realize the rapid conversion of Li2S6. Moreover, the impact of lithium‐ion diffusion on the reactions in the cell is investigated, and the mechanism of Ni3S2@C in the cell is proposed based on the “ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…5h and listed in Table S2. † 8,14,15,[48][49][50][53][54][55][56][57][58][59][60][61][62][63][64] To fulll the demand for practical applications of Li-S batteries, the electrochemical performance at high sulfur loading was investigated. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5h and listed in Table S2. † 8,14,15,[48][49][50][53][54][55][56][57][58][59][60][61][62][63][64] To fulll the demand for practical applications of Li-S batteries, the electrochemical performance at high sulfur loading was investigated. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They accurately tracked the volumetric and micro−morphological changes of the active material particles during the charge−discharge process using in situ SEM and energy−dispersive X−ray spectroscopy while repeatedly disassembling the battery electrodes. Zhang et al 175 visualized the changes of polysulfides in symmetric batteries through in−situ optical image visualization. Additionally, they examined the adsorption effect of the Ni 3 S 2 @C Separator on LiPSs by configuring different concentrations of electrolytes.…”
Section: LImentioning
confidence: 99%
“…[7] Zhang et al reported on the fabrication of Ni 3 S 2 nanoparticle electrocatalysts with abundant active sites, which are capable of strengthening the chemical affinity of LiPSs and boosting their reaction kinetics based on the "adsorptiondiffusion-conversion" mechanism. [8] To further upgrade the Li-S battery performance in terms of the high-rate capability and long cycling stability, several efficient methods, including the anion defects, [9] heterointerface engineering, [10] and cation doping strategy [11] , etc., have been demonstrated to greatly improve the adsorption and catalytic conversion of LiPSs on the TMS with tailored surface/interface structure. Although these advances, the electrochemical performance of Li-S batteries with different kinds of TMSs varies considerably, the intrinsically active descriptor of these TMSs and their surface/interface structureactivity relationship for Li-S batteries are still not well revealed.…”
Section: Introductionmentioning
confidence: 99%